Senescence-associated protein p400 is a prognostic marker in renal cell carcinoma - Macher-Göppinger, Stephan; Lorenzo Bermejo, Justo; Schirmacher, Peter; Pahernik, Sascha; Hohenfellner, Markus; Roth, Wilfried (Oncology reports, 2013)
Mutations of the von Hippel-Lindau (VHL) tumor suppressor gene cause hereditary and sporadic renal cell carcinomas (RCCs). The best characterized function of VHL protein is suppression of the α subunit of hypoxia inducible factor (HIF). Additional VHL functions have been reported, including induction of senescence upon loss of VHL mediated by downregulation of the chromatin remodeling factor p400. Induction of senescence either by oncogene activation or inactivation of tumor suppressors is considered a critical feature of mammalian cells by which to suppress tumorigenesis. In the present study, we investigated the relationship between the expression of p400 and patient survival following RCC diagnosis taking advantage of a large and well-documented series of RCC patients with long-term follow-up information. The expression of p400 was measured by immunohistochemistry using a tissue microarray containing tumor tissue samples from 868 RCC patients. Chi-squared tests, Kaplan-Meier curves, Cox regression models and Spearman's rank correlation estimates were used to investigate the possible relationship between p400 expression and Ki-67 proliferative index, clinical and pathological characteristics and patient survival. Complete loss of p400 expression was detected in 64% of all tumor specimens, and decreased p400 expression was associated with advanced tumor stage, higher grade of malignancy and regional lymph node metastasis. Among well-differentiated RCCs, high proliferation (Ki-67 index >10) was found in 12% of carcinomas with an increased p400 expression, compared to 5% of RCCs with decreased p400 expression. Multiple Cox regression indicated that patients with low proliferative tumors and increased p400 expression had a 60% lower cancer-specific mortality risk compared to those affected by low proliferative RCCs with decreased p400 expression. In summary, patients affected by highly proliferative tumors with decreased p400 expression exhibit a poor prognosis by multiple Cox regression. Our data suggest that the highly proliferative, decreased-p400 subgroup of RCCs represents tumors that are characterized by a loss of the tumor-suppressive mechanism of senescence.